(untitled) (Revista Internacional de Folkcomunicação, 2020)
The Olubajé rituals show symbolic values ​​that make up the universe that circulates around the mythology of the Orixá Omolú. To elaborate this article, the research is based on the observation and phenomenological method (MASSINI, 1989) and adopts the view through discursive analysis (FOUCAULT, 1996) as a methodological device of the dynamics of the utterances made by the priestess responsible for the Temple of Religion Africana Ilè Àsé Iyá Ogunté, in the municipality of Ananindeua, in the state of Pará, at the Olubajé party that takes place with the main interest of thanking for the restoration of the health of the temple priestess. The purpose of this text is to describe and analyze the Olubajé party dedicated to the orixá Omolú, as well as to evaluate the symbologies related to the event related to the mythological narratives of the orixás (PRANDI, 2012).. Candomblé; Olubajé; Discourse analysis; Narratives.